2016
DOI: 10.7589/2015-01-007
|View full text |Cite
|
Sign up to set email alerts
|

Pathology and Molecular Detection of Rabies Virus in Ferret Badgers Associated With a Rabies Outbreak in Taiwan

Abstract: Until Rabies virus (RABV) infection in Taiwan ferret badgers (TWFB; Melogale moschata subaurantiaca) was diagnosed in mid-June 2013, Taiwan had been considered rabies free for >50 yr. Although rabies has also been reported in ferret badgers in China, the pathologic changes and distribution of viral antigens of ferret badger-associated rabies have not been described. We performed a comprehensive pathologic study and molecular detection of rabies virus in three necropsied rabid TWFBs and evaluated archival paraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The recent study performed the pathologic and molecular detection of rabies virus in three Taiwan FBs and found that the earliest infected case could be traced back to 2004. In these FBs nonnervous system tissues, representative lesions included adrenal necrosis and lymphocytic interstitial sialadenitis [9]. The higher seroprevalence of rabies infection in FBs reported in Mainland China [3] also implied that FBs may be less capable reservoir animals in comparison to other wild carnivores for rabies transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The recent study performed the pathologic and molecular detection of rabies virus in three Taiwan FBs and found that the earliest infected case could be traced back to 2004. In these FBs nonnervous system tissues, representative lesions included adrenal necrosis and lymphocytic interstitial sialadenitis [9]. The higher seroprevalence of rabies infection in FBs reported in Mainland China [3] also implied that FBs may be less capable reservoir animals in comparison to other wild carnivores for rabies transmission.…”
Section: Discussionmentioning
confidence: 99%
“…2). Chiou et al [5] found 97-99% nucleotide identity of the N gene of rabies virus within three isolates from Taiwan Ferret Badgers. Jamil et al [8] revealed 98-100% nucleotide identity between N gene sequences of rabies virus from seven brain samples.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Taiwan had been globally recognized as rabies-free since 1961. However, in 2011, the disease surveillance program was expanded to include native wildlife, and in 2013 three dead ferret badgers (Melogale moschata) tested positive for rabies virus by fluorescent antibody testing [60,61]. This new detection indicated that despite the lack of dog or human cases, rabies virus had silently remained in circulation within the wildlife population of Taiwan.…”
Section: Bat Rabies Surveillance Effortsmentioning
confidence: 99%